SUCNR1 Is Expressed in Human Placenta and Mediates Angiogenesis: Significance in Gestational Diabetes - Reham Atallah (MDPI AG, 2021)
Placental hypervascularization has been reported in pregnancy-related pathologies such as gestational diabetes mellitus (GDM). Nevertheless, the underlying causes behind this abnormality are not well understood. In this study, we addressed the expression of SUCNR1 (cognate succinate receptor) in human placental endothelial cells and hypothesized that the succinate–SUCNR1 axis might play a role in the placental hypervascularization reported in GDM. We measured significantly higher succinate levels in placental tissue lysates from women with GDM relative to matched controls. In parallel, SUCNR1 protein expression was upregulated in GDM tissue lysates as well as in isolated diabetic fetoplacental arterial endothelial cells (FpECAds). A positive correlation of SUCNR1 and vascular endothelial growth factor (VEGF) protein levels in tissue lysates indicated a potential link between the succinate–SUCNR1 axis and placental angiogenesis. In our in vitro experiments, succinate prompted hallmarks of angiogenesis in human umbilical vein endothelial cells (HUVECs) such as proliferation, migration and spheroid sprouting. These results were further validated in fetoplacental arterial endothelial cells (FpECAs), where succinate induced endothelial tube formation. VEGF gene expression was increased in response to succinate in both HUVECs and FpECAs. Yet, knockdown of SUCNR1 in HUVECs led to suppression of VEGF gene expression and abrogated the migratory ability and wound healing in response to succinate. In conclusion, our data underline SUCNR1 as a promising metabolic target in human placenta and as a potential driver of enhanced placental angiogenesis in GDM.